PERBANDINGAN PELARUT ETANOL DAN AIR PADA PEMBUATAN EKSTRAK UMBI BAWANG TIWAI (Eleutherine americana Merr) MENGGUNAKAN METODE MASERASI - Hayatus Sa'adah; Henny Nurhasnawati (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2015)
Bawang tiwai (Eleutherine americana Merr) is one kind of medicinal plant. To obtain an active substances with good physical and chemical properties, it is needs to do optimization of making extracts, one with solvent optimization. Type of solvent will determine the types of extracted substances in accordance with the polarity. On this research, extraction of bawang tiwai bulbs simplicia by maceration method using ethanol and water as solvent. This research is an experimental research with varying ethanol and water in a three comparison solvent that is water, ethanol, and mixture of water-etanol, then the yields is calculated. Furthermore, the data were analyzed statistically using ANOVA program to determine significant differences in the three yields. In each extract was conducted phytochemical screening to determine the content of secondary metabolites. The results showed significant differences in the yield of bawang tiwai extract with three treatments and two repetitions. The results of average yields using water as solvent is 8.75%, ethanol 5.3%; and water-etanol 8.31%